Creating a 'FatherConfessor': the origins of research ethics committees in UK military medical research, 1950–1970. Part II, origins and organisation. Issue 4 (4th August 2019) - Schmidt, Ulf
Abstract : Using a major ethics crisis as a methodological approach to study secret science environments, part II examines the origins and organisation of the Applied Biology Committee (ABC), the first independent research ethics committee (REC) at Porton Down, Britain's biological and chemical warfare establishment since the First World War. Although working in great secrecy, the UK military, and Porton in particular, did not operate in a social, political and legal vacuum. Paradigm shifts in civilian medical ethics, or public controversy about atomic, chemical and biological weapons, could thus influence Porton's self-perception and the conduct of its research. The paper argues that the creation of the first REC at Porton in 1965, that is, the ABC, as the ' father confessor ' inside the UK's military research establishment reflected a broader paradigm shift in the field of human research ethics in the mid-1960s.